Research on the applicability of international databases to fossil fuel emission in China. Issue 3 (4th May 2018) - Shang, Li; Wang, Maohua; Wang, Mingquan; Li, Qingqing; Wei, Wei
ABSTRACT: The accuracy of carbon emissions statistics is a prerequisite for low-carbon development research. There are nearly 10 institutions in the world that have conducted in-depth studies on the carbon emissions of various countries; however, the accounting results of different databases are not the same and the analyses mainly focus on qualitative comparison. In order to clarify the source of databases' difference in practical application, a quantitative applicability evaluation methodology has been built, which takes the data's scope, consistency and authority as the criterion, and combines the analytic hierarchy process and fuzzy integrated evaluation, enabling an applicability analysis of different databases on parameter level. Based on the emission characteristics of fossil fuel in China, the evaluation system has been applied to four core databases. The corresponding applicability to China, in descending order, is the International Energy Agency (IEA), Emissions Database for Global Atmospheric Research (EDGAR), Energy Information Administration (EIA) and Carbon Dioxide Information Analysis Center (CDIAC). Furthermore, by identifying the advantages/disadvantages of databases' accounting of China's emissions, several suggestions on activity data, emission coefficients and supporting evaluation are proposed, aiming to provide references for the construction of a comprehensive database on carbon emissions in China.